Fried Feathers for Thanksgiving - Stevenson, James (scholastic New York, 1986)
Mean witches Folores and Lavinia try to spoil Thanksgiving for everyone else but nice witch Emma and her friends outwit them.
Keywords: Witches -- fiction; Thanksgiving -- fiction